Expertise, working memory and articulatory suppression effect: Their relation with simultaneous interpreting performance - Injoque Ricle, Irene (2015)
Simultaneous interpreting is a complex bilingual verbal activity that involves the auditory perception of an oral communication and the production of a coherent discourse. One of the cognitive functions underlying simultaneous interpreting is working memory. The aim of this work was to study the relationship between expertise, working memory capacity and articulatory suppression effect, and the ability to perform simultaneous interpreting. For this purpose, four working memory tasks and one simultaneous interpreting task were administered to thirty Spanish-speaking professional English interpreters. Results showed that simultaneous interpreting ability might be supported by the working memorýs capacity to store or process information, but also by the ability of the interpreter to cope with the articulatory suppression effect. We conclude that interpreters may have or develop resources to support the effect caused by articulatory suppression.